Analisis Framing Pemberitaan Pembunuhan Brigadir J di Media Online CNNIndonesia.com - Amrin, Amrin (Kanal: Jurnal Ilmu Komunikasi, 2024)
This research aims to find out how the framing was carried out by CNNIndonesia.com in reporting on the murder case of Brigadier J, July 11-12 2022 edition. This research uses a qualitative description approach with Robert N Entman's framing analysis method, where Entman's framing analysis includes four stages: Define problem , Diagnose cause, Make moral Judgment, and Treatment recommendation. The results of the research show that, Define problem, disclosure of the murder case of Brigadier J. Diagnose cause is that the police believe that Brigadier J's death was motivated by sexual harassment towards the wife of the Head of the National Police Propam Division, Inspector General Ferdy Sambo. Make a moral judgment where the police emphasize Brigadier J's immoral behavior and temperament which has sexually harassed Ferdy Sambo's wife. Treatment recommendation, CNNIndonesia.com emphasizes two solutions, namely: first, the Police through the South Jakarta Metro Police and the Police Propam Division to continue to investigate the case of Brigadier J's death. Second, encourage the formation of a joint fact-finding team (TGPF) to uncover the case of his death. Brigadier J..